Определение полезной нагрузки трубчатых печей с помощью учета тепловых потерь в системе теплообмена на установке первичной переработки нефти АВТ А12/2 в режиме работы без вакуумного блока - Ульев, Леонид Михайлович; Мельниковская, Лиана Александровна (НТУ "ХПИ", 2011)
To determine the exact values of the payload of ovens and interaction utilities with a process it is necessary to take into account the flow of heat losses in the heat exchange equipment and pipes. This flow is included in the stream data table and used in the construction of large composite curve of the process of primary oil refining in the AVDU A12/2 in the mode of operation without a vacuum unit.
Keywords: энергоносители; энергопотребление; нефтеперерабатывающая промышленность; атмосферно-вакуумная трубчатка; тепловые потери; вакуумный блок; теплообмен; нефтепереработка